EFL Undergraduate Students' Cognitive Strategies in Process-Based Writing - Arliyanti, Devi; Hapsari, Astri (Pioneer: Journal of Language and Literature, 2022)
Even though process-based writing has been extensively researched and implemented in higher education, little is known about how cognitive strategies are implemented in process-based essay writing. This study investigated how EFL undergraduate students used writing strategies in English essays. The process of writing was investigated by using cognitive theory in this semi-structured interview qualitative research. The two participants were English language education department batch 2019 students from a private university in Yogyakarta who had completed their processes-based essay writing final project when the study was conducted. The findings revealed that Rara and Kevin (the participants' pseudonyms) used different writing strategies in the essay writing process planning stage. Rara organised her writing using the outline, whereas Kevin used keywords to organise his writing. This study implied that when teaching process-based essay writing, a language teacher or lecturer should be aware of the different stages of the student's cognitive strategies, especially during the planning stage.